Some considerations regarding the proper name - González F., Diana (Lengua y Sociedad, 2004)
The proper name is a linguistic phenomenon that is part of the most relevant social institutions. Given its wide use in all domains of human life, it is - the object of study not only of linguistics, sociology, psychology, anthropology, but - also of ethnology, theology and jurisprudence.